The Instructional Design Of English Teaching At Smk Bina Patria I Sukoharjo: A Micro Ethnographic Study - Kuswahyuningsih, Kuswahyuningsih; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
English has become major device as a bridge of international communication. The existence of instructional design is a recent issue in English teaching specially in Vocational High School. The research problem of the study is how the instructional design of English teaching at SMK Bina Patria 1 Sukoharjo. The objectives of the study reveal briefly of instructional design of English teaching at SMK Bina Patria I Sukoharjo in which encompasses syllabus, learning objective, instructional material, teaching design, evaluation and strengths-weaknesses of English teaching. The research was an ethnographic study. The efforts of study overview notional-functional syllabus which categorized into novice, elementary, intermediate level. The learning objectives are general and specific learning outcome. The instructional material is divided into printed, audio and visual material. Teacher's roles are facilitator, observer, organizer, and explainer. The student's roles are processor, performer, and listener. The classroom procedure is three patterns namely: BKOF-MOT-JCOT-ICOT, BKOF-MOT-JCOT, and BKOF-MOT-JCOT. The classroom activities are advance organizer, presentation, classroom practice, role play, comprehension, answer question and reading aloud. The media are grouped into two forms. The first is printed media such as picture, rainbow envelop and colorful letter. The second is unprinted media entails slide, cassette and compact disk. The evaluation describes evaluation model and kind of evaluation. The evaluation models are dialogue completion task, multiple choice and cloze procedural text. The kind of evaluation involves formative and summative evaluation. There are strength and weakness among the instructional design of English teaching at SMK Bina Patria 1 Sukoharjo. Departing with the finding, discussion, conclusion and implication, the writer suggests for English teacher to encourage students' engagement in the classroom. The application of diverse methods and techniques are obviously required in English teaching. The writer also recommends for future researcher to expand the study in other research field